ISTIRATIJIYYAT MU’ALLIM AL-LUGHAH AL-‘ARABIYYAH ‘INDA TAGHALLUBI SU’UBAH QIROAAT AN-NUSUUS AL-‘ARABIYYAH ‘ALAA THULLAABI AS-SHAFI AL-'AASYAR FII AL-MADRASAH AL-'ALIYATI AL-MUHAJIRIN CIGUDEG (DIRAASAH HAALIYAH 'AN MADDAH AL-LUGHAH AL-'ARABIYYAH) - Taufan Al-Farisi; Muh Abrar; Lukman Taufik Akasahtia (Program Studi Pendidikan Bahasa Arab, 2022)
This research provides benefits for Arabic language teaching lecturers in helping to provide an easy learning motivation for students to master and memorize the Qur’an through learning the Arabic language. That the author of this research be able to provide benefits in applying and applying Arabic language proficiency in memorizing the Qur’an. It can be a positive contribution and as a material consideration, especially for the educational institutions of the Jahai Quran Jebonbulang Bogor High School in improving Arabic language learning towards fluency in Quran memorization. The researchers want to further research on the comparison between the application of learning the Arabic language, especially in speaking skills with the lack of application of learning the Arabic language, especially in speaking skills, to the fluency of memorizing the Qur’an in this Quran memorization institute. Based on the above research results, learning Arabic has a significant impact on the fluency of memorizing the Qur’an, especially for students who master the ability to speak Arabic. It is therefore hoped that this ability to speak in the future will become a second priority in addition to memorizing the Qur'an, in order to facilitate the memorization of the Qur'an for students